Effect of chlorhexidine, honey and Propolis on Streptococcus mutans Counts: in vitro Study - Abdulrhman Alkhaled; Laith Alsabek; Maher Al-assaf; Faek Badr (University Library System, University of Pittsburgh, 2021)
Objective: .Streptococcus mutans is considered one of the bacteria that causes necrosis, as it metabolism sugar to obtain energy, producing an acidic environment and causing depression in the enamel surface, which causes the dissolution of the calcium molecule, a problem of cavited in the tooth; so the aim of the research is to evaluate the effect of mouthwashes chlorhexidine 0.12% - honey 50% - propolis 5% on Streptococcus mutans in children. Study design: A laboratory study to assess the efficiency of chlorhexidine, honey and Propolis on Streptococcus mutans counts. The sample included 60 children divided into: G1 (Chlorhexidine 0.12% = 20 children), G2 (Propolis 5% = 20 children), G3 (Honey 100% = 20 children). The data was analyzed using the statistical analysis program SPSS, version 13.00, at a confidence level of 95% (P <0.05(. Paired sample T test was used to compare the variable means of the values of the studied variables. Results: There is significant difference between  three groups. The reduction ratio was 89.97% in G1, 85.49% in G2 and 76.29% in G3. Conclusion: This study demonstrated the effectiveness of mouthwashes of chlorhexidine, propolis and honey on the bacteria of Streptococcus mutans.